2019
DOI: 10.1093/cdn/nzz108
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Serum Magnesium Concentrations among Women with Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) affects ∼1 in 10 women worldwide. Hypomagnesemia may worsen insulin resistance (IR) due to the role magnesium (Mg) plays in glucose metabolism. This review explores the relation between serum Mg and IR among women with PCOS. A review of primary research focusing on both serum Mg and women with PCOS was conducted from 2011 to 2019. Studies reviewed included human subjects, written in the English language, and limited to community-dwelling women aged ≥18 y. A total of 7 articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
(164 reference statements)
2
20
0
1
Order By: Relevance
“…Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders, affecting 4–10% of the women of reproductive age [ 1 , 2 ]. The clinical symptoms of PCOS include irregular menstrual cycles, infertility, hirsutism, acne, insulin resistance (IR), and hyperandrogenemia [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders, affecting 4–10% of the women of reproductive age [ 1 , 2 ]. The clinical symptoms of PCOS include irregular menstrual cycles, infertility, hirsutism, acne, insulin resistance (IR), and hyperandrogenemia [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a significant association between hypomagnesaemia and new-onset diabetes after kidney transplantation (NODAT), in kidney transplant recipients, for both adult and pediatric patients has been indicated. Moreover, murine studies have shown that the maternal hypomagnesaemia is associated with diabetes mellitus, insulin resistance, dyslipidemia, metabolic syndrome, depression, impaired placental development, impaired fetal growth and increased mortality [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Bottled water may be an essential and inexpensive source of magnesium and other minerals.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] Evidence reveals that weight reduction by as little as 5%, potentially improves ovulation cycles and restores normal menstruration. 52 The use of exercise regimens such as Hiit and steady training are shown to improve insulin sensitivity. 50 Physical activities may also have some benefits on psychological manifestations as it helps to improve states of depression and anxiety.…”
Section: Managementmentioning
confidence: 99%
“…57 Therefore, the use of supplements in the form of vitamins or minerals may be used to complement the treatment of PCOS. 52 Vitamins such as vitamins A,B,D,E or inositol has antioxidant properties which have several potential benefits including: 1) help in oocyte maturation, 2) decrease cardiovascular risk factors, 3) improve menstruation, 4) improve fertility, 5) improve endometrial lining thickness, and 6) reduce androgen levels. Minerals such as calcium, chromium and zinc, may also contribute to improvements in ovulatory cycles, menstruation, and metabolic profiles in patients diagnosed with PCOS.…”
Section: Managementmentioning
confidence: 99%